2005
DOI: 10.1081/ncn-200059277
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation of Biotin During Oligonucleotide Synthesis

Abstract: A new "polystyrene biotin support" has been synthesized for the solid support synthesis of the 3'-biotinylated oligonucleotides. Several oligos were synthesized and were analyzed by the HPLC and Mass Spec. Oligo analysis revealed that the biotin gets oxidized to "biotin sulfoxide" during the synthesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
6
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 5 publications
1
6
0
Order By: Relevance
“…During purification of the products by RP‐HPLC, closely eluting by‐products with a molecular mass 16 Da higher than that of the expected product RNA were observed. These were attributed to oxidation of the sulfur atom on the biotin moiety;13 as this is consistent with a previous report of biotin oxidation during oligonucleotide synthesis, which presumably occurred during the P III oxidation step 14. Thus, oligoribonucleotides 1 and 2 (Table 1) were oxidized to 3 and 4 , respectively, thus indicating that the phenomenon was not sequence dependent (Figure S1 in the Supporting Information).…”
Section: Oligoribonucleotides Used In the Studysupporting
confidence: 87%
“…During purification of the products by RP‐HPLC, closely eluting by‐products with a molecular mass 16 Da higher than that of the expected product RNA were observed. These were attributed to oxidation of the sulfur atom on the biotin moiety;13 as this is consistent with a previous report of biotin oxidation during oligonucleotide synthesis, which presumably occurred during the P III oxidation step 14. Thus, oligoribonucleotides 1 and 2 (Table 1) were oxidized to 3 and 4 , respectively, thus indicating that the phenomenon was not sequence dependent (Figure S1 in the Supporting Information).…”
Section: Oligoribonucleotides Used In the Studysupporting
confidence: 87%
“…The identity of the product was confirmed via liquid chromatography electrospray ionization mass spectrometry analysis on a Thermo Scientific LCQ FleetTM electrospray ionization spectrometer equipped with an Eclipse XDB-C18 5-m column from Agilent, Santa Clara, CA and using a linear gradient of solvent B (5 mM NH 4 OAc in acetonitrile) in solvent A (5 mM NH 4 OAc in H 2 O) at a flow rate of 1 ml/min (gradient program: 0 min/10% B 3 1 min/10% B 3 10 min/100% B 3 12 min/100% B 3 15 min/10% B). At R t ϭ 2.16 min, calculated for C 26 Labeling with BHAcATP-Arabidopsis proteome was extracted from 4-week-old Arabidopsis rosette in 50 mM Tris pH 7.5. The lysate was cleared via centrifugation and subjected to gel filtration using DG10 columns (Bio-Rad).…”
Section: Methodsmentioning
confidence: 99%
“…In addition to the biotinylated solid support 120b, another version, 120j, containing a protected biotin pendant, R 42 , was introduced (Upadhya et al, 2005). This study identified a side reaction, an oxidation of the sulfide moiety of biotin to the respective sulfoxide during the course of oligonucleotide chain assembly on solid support 120j.…”
Section: 134mentioning
confidence: 99%